PENGARUH KUALITAS LAYANAN DAN PENGALAMAN PENGGUNA TERHADAP MINAT PENGGUNAAN ULANG DENGAN KEPUASAN PENGGUNA SEBAGAI VARIABEL INTERVENING PADA KONSUMEN GRAB BIKE DI KOTA SEMARANG (Studi pada Mahasiswa Universitas Diponegoro) - Parahita, Dyaksa Witsqa; Raharjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT Research was only conducted on the influence of service quality and user experience on reuse intentions with user satisfaction as a intervening variable for Grab Bike consumers in Semarang City. This research aims to determine the influence of service quality and user experience on reuse intentions with user satisfaction as a mediating variable among Grab Bike consumers in Semarang City. The population in this study were Undip students who used Grab bikes in the city of Semarang. This research used a positive sampling technique, where samples were taken based on criteria, obtaining a total of 130 respondents. Data collection uses a questionnaire by distributing a list of questions to respondents to obtain information. The analysis technique in this research uses Structural Equation Modeling (SEM) with AMOSS Software 25. The results of the research are: service quality has a positive and significant influence on intention to reuse, service quality has a positive and significant influence on user satisfaction, user experience has a positive and significant influence on intention to reuse, user experience has a positive and significant influence on service user satisfaction , and user satisfaction have a positive and significant influence on reuse intentions.